Sensory Phenomenon Assessment Scale: a new tool for assessment of tic-associated sensations - Wang, Xianbin; Li, Yanlin; Yu, Liping; Xu, Hui; Zhang, Anyi; Zhang, Wenyan; Jiang, Zhongliang; Cui, Yonghua; Li, Ying (Frontiers in Psychiatry, 2024)
Background Sensory symptoms linked to tic disorder (TD) are challenging to quantify via self-or parent-reported measures. The current study aimed to develop a novel observer-rated semi-structured interview, namely the Sensory Phenomenon Assessment Scale (SPAS), to aid clinical evaluation on symptoms of tic disorder among children.To test its psychometric properties, tic, premonitory urge (PU) and obsessive-compulsive symptoms (OCS) were also assessed in 223 children via the Yale Global Tic Severity Scale (YGTSS), Premonitory Urge for Tic Scale (PUTS) and the Children's Yale-Brown Obsessive-Compulsive Scale (CY-BOCS). Factor analysis and internal consistency test were carried out using data from TD-diagnosed individuals.Good internal consistency and test-retest reliability were observed. Criterion validity was established by significant correlations between the PUTS, the YGTSS, the CY-BOCS, and scores of the SPAS. Factor analyses supported a single-factor model of the SPAS, in which the 5 items each showed a factor loading above 0.6.This study demonstrated that the SPAS is reliable and valid, thus can serve as a good and concise measure of clinical symptoms among children and adolescents with tic disorder.